Pengunaan Media Audio Visual dalam Meningkatkan Kemampuan Membaca Siswa pada Mata Pelajaran Bahasa Indonesia - Giyanti, Giyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research was to improve students' reading ability in Bahasa Indonesia subjects in grade 1 students at SDN 02 Ujan Mas by using Audio visual media. This research uses a type of Class Action (PTK) research conducted in 2 cycles, each cycle consists of 4 stages, namely the stage of planning, implementation of actions, observation and reflection. This research subsection is all 24 students in grade 1B. Data collection techniques are carried out through tests, and observations. Data analysis is done through observation data management. As a result of the study, it is known that students' reading ability is still very low because the average score of new students reaches 59.62 and the completion of new students' learning outcomes reaches 33.33, in the first cycle that the test results mangalami improvement, before the student improvement is complete is 8 students (33.33%), increased to 12 students (50.00%) with an average score of 1,611 or an increase of 4 students (19, 04%). and the second cycle pad increased drastically with an average score of 1,718 and a complete number of 19 students with a completion percentage of 79.16%. In conclusion, the use of audiovisual media effectively improves the reading ability of grade 1 students in Indonesian language subjects at SD Negeri 02 Ujan Mas. Keywords: Indonesian Language, Reading Ability, Audio Visual Media.